Islamic Law Perspective in Viewing the Implementation of Friday Prayer in the Workplace or Not a Mosque When the COVID-19 Pandemic Happened - Efrinaldi (Global Writing Academica Researching & Publishing, 2022)
This research was conducted to see how it is legal to perform Friday prayers in places that are not mosques, such as offices or other workplaces such as halls, prayer rooms, and the field during the Covid-19 pandemic. This research is part of qualitative research that uses descriptive methods using data derived from various research results and previous studies that still have relevance to this research. This study found that the law of carrying out Friday prayers in a place that is not a mosque during a pandemic is permissible. This law refers to various verses of the Qur’an, hadiths, and rules in the science of fiqh to various opinions of scholars. However, if there is a mosque that is still close to and can accommodate the entire congregation after the distance between the prayer rows, it is more advisable to be able to pray in that mosque.